2017
DOI: 10.4271/2017-01-2165
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Pose Control of an Industrial Robotic System for Machining of Large Scale Components in Aerospace Industry Using Laser Tracker System

Abstract: The high demand of efficient large scale machining operations by concurrently decreasing operating time and costs has led to an increasing usage of industrial robots in contrast to large scaled machining centers. The main disadvantage of industrial robots used for machining processes is their poor absolute accuracy, caused by the serial construction, resilience of gearings and sensitivity for temperature changes. Additionally high process forces that occur during machining of CFRP structures in aerospace indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 7 publications
0
21
0
1
Order By: Relevance
“…Work on real time pose control of an industrial robot using 3-DoF and 6-DoF laser tracking has also been reported by Moeller et al [99]. Fig.…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…Work on real time pose control of an industrial robot using 3-DoF and 6-DoF laser tracking has also been reported by Moeller et al [99]. Fig.…”
Section: Methodsmentioning
confidence: 78%
“…External guidance (Fig. 29) makes the machining robot unsusceptible to external or constant process forces, thermal expansion and calibration errors [99].…”
Section: Sensor Based Programming Methods (Deburring Polishing)mentioning
confidence: 99%
“…The model is modified by adding virtual joints at the end effector to take into account the compliance of the force/torque sensor (9), the spindle and its holder (10) as well as the tool (13). The accurate orientation of the tool is calculated by an Euler rotation from coordinate system (11) to (12).…”
Section: Compliance Modelmentioning
confidence: 99%
“…One possibility is the monitoring and correction of the TCP position, which is realized by very cost-intensive position measuring technology, e.g. laser trackers [8,12,15]. Second encoder systems, which measure the axis position on the load side in addition to the motor side system, can be used to compensate torsional compliance and gear backlash [7,9].…”
Section: Introduction and State Of The Artmentioning
confidence: 99%
“…It requires the machining robots not only to have good machining performance but should be equipped with relevant measuring system to assist the robots to locate the machining position of workpiece. [1][2][3][4] The commonly used measuring system in industry can be divided into contact measurement and noncontact measurement. Due to the complex and irregular surface profile of the workpiece, the contact measuring system is difficult to meet the needs of industry.…”
Section: Introductionmentioning
confidence: 99%